2023
DOI: 10.1177/00031348231173947
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Increasing Number and Cost of Residency Applications in Surgery

Abstract: Background Surgical specialties represent the most competitive residency positions to obtain, and applicants for these spots may apply to increasingly more programs in an attempt to match. We describe trends in residency applications across all surgical specialties from 2017 to 2021 application cycles. Materials and Methods This review of the 2017, 2018, 2019, 2020, and 2021 surgical residency application cycles used the American Association of Medical Colleges’ Electronic Residency Application Service (ERAS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Such pressures are only heightened in the wake of the United States Medical Licensing Examination (USMLE) Step 1 examination transitioning from a numeric score to pass/fail grading as students seek to distinguish themselves among a competitive applicant pool 42 . In light of these changes, programs have been forced to consider alternative methodologies of ranking applicants and looking to new metrics to differentiate students 5,43–46 . As plastic surgery applicants are evaluated, it is essential to consider how these metrics may exacerbate inequalities in the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pressures are only heightened in the wake of the United States Medical Licensing Examination (USMLE) Step 1 examination transitioning from a numeric score to pass/fail grading as students seek to distinguish themselves among a competitive applicant pool 42 . In light of these changes, programs have been forced to consider alternative methodologies of ranking applicants and looking to new metrics to differentiate students 5,43–46 . As plastic surgery applicants are evaluated, it is essential to consider how these metrics may exacerbate inequalities in the system.…”
Section: Discussionmentioning
confidence: 99%
“…The UIM students or those who come from institutions with no plastic surgery home programs may find it more challenging to develop a strong mentorship relationship and thus may be unable to access these opportunities 48 . During this same period, the number of applications per applicant and the total cost of applying to plastic surgery have dramatically increased, which again may disadvantage UIM applicants 44,50 . As plastic surgery training and the application process continues to evolve, we must be aware of the possible inequities it may foster and how it affects the future of our specialty.…”
Section: Discussionmentioning
confidence: 99%
“…This trend has been observed in other surgical fields such as orthopedic surgery, neurosurgery, otolaryngology, and urology. 30 In addition, the total number of applications increased by nearly half (45%). These findings suggest that there is a widespread instability in the current plastic surgery application process, which merits investigation to quell both the burden of time and cost associated with such high levels of applications.…”
Section: Discussionmentioning
confidence: 99%
“…Programs could subsequently engage in holistic review which has been shown to diversify the pool of applicants selected for interviews. 1 Reducing the number of applications submitted would also be financially advantageous to the applicant-many of whom accrue significant debt during the residency application and recruitment process 2,12 and may decrease barriers for applicants from lower socioeconomic backgrounds.…”
Section: Introductionmentioning
confidence: 99%